Putting the Mess in Order: Aspergillus welwitschiae (and Not A. niger) Is the Etiological Agent of Sisal Bole Rot Disease in Brazil - Duarte, Elizabeth A. A.; Damasceno, Caroline L.; de Oliveira, Thiago A. S.; Barbosa, Leonardo de Oliveira; Martins, Fabiano M.; de Queiroz Silva, Jurema Rosa; de Lima, Thais E. F.; da Silva, Rafael M.; Kato, Rodrigo B.; Bortolini, Dener E.; Azevedo, Vasco; Góes-Neto, Aristóteles; et al. (Frontiers in Microbiology, 2018)
Approximately 75% of the worldwide production of hard natural fibers originates from sisal, an industrial crop from arid and semiarid tropical regions. Brazil is the world's largest producer of sisal fiber, accounting for more than 40% of the worldwide production, and sisal bole rot disease has been the main phytosanitary problem of this crop. All previous studies reporting Aspergillus niger as the causal agent of the disease were based on the morphological features of fungal isolates from infected plant tissues in pure cultures. Black aspergilli are one of the most complex and difficult groups to classify and identify. Therefore, we performed an integrative analysis of this disease based on the isolation of black aspergilli from the endospheres and soils in the root zones of symptomatic adult plants, in vivo pathogenicity tests, histopathology of symptomatic plants, and molecular phylogeny and worldwide genetic variability of the causal agent. All sisal isolates were pathogenic and unequivocally produced symptoms of bole rot disease in healthy plants. In all tree-based phylogenetic methods used, a monophyletic group formed by A. welwitschiae along with all sisal isolates was retrieved. Ten A. welwitschiae haplotypes have been identified in the world, and three occur in the largest sisal-producing area. Most of the isolates are from a unique haplotype, present in only the sisal-producing region. A. welwitschiae destroyed parenchymatic and vascular cylinder cells and induced the necrosis of internal stem tissues. Therefore, sisal bole disease is probably the consequence of a saprotrophic fungus that opportunistically invades sisal plants and behaves as a typical necrotrophic pathogen.